â€œBlack Boxâ€ between Authentic Leadership and Follower Commitment - Heru, Tri; Haryokusumo, Diaz (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
The aims of present study was to test the theoritical linking model of authentic leadership with personal identification, social identification, trust to leader, and organizational commitment in higher education institution. The quantitative methodology used in this study incorporates cross-sectional survey method. Analysis was conducted on the sample of 150 academic and administrative staff from one of private business school in Yogyakarta special region. The direct effect between variables analyzed using path analysis and mediating mechanism using procedure from Baron and Kenny (1986) and Sobel test.Â Results reveal positive and significant direct effect of authentic leadership to personal identification, social identification, trust to leader and organizational commitment. Folowerâ€™s personal identification mediate the effect of authentic leadership to followerâ€™s trust and commitment. Followerâ€™s trust to leader mediate the relationship between authentic leadership and followerâ€™s commitment. Meanwhile, social identification does not mediate the effect of authentic leadership to followerâ€™s commitment and trust to leader. Implication for management theory and practice are discussed.